2012
DOI: 10.1007/s11412-012-9145-0
|View full text |Cite
|
Sign up to set email alerts
|

How to improve collaborative learning with video tools in the classroom? Social vs. cognitive guidance for student teams

Abstract: Digital video technologies offer a variety of functions for supporting collaborative learning in classrooms. Yet, for novice learners, such as school students, positive learning outcomes also depend centrally on effective social interactions. We present empirical evidence for the positive effects of instructive guidance on performance and on learning of students who use web-based video tools during a short collaborative-design task in their history lesson. In an experiment with 16-year old learners (N0148) wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…In this study, the application did not build in any capability to point out incorrect scientific facts or explanations for students. Additionally, to facilitate understanding of the dynam-ics of the argumentation process, researchers' intervention was intentionally minimal in this study (Asterhan, Schwarz, & Gil, 2012;White & Dinos, 2010;Zahn, Krauskopf, Hesse, & Pea, 2012). However, both researchers intervened in the process when the students were off-task or off-topic.…”
Section: Solar Teammentioning
confidence: 99%
“…In this study, the application did not build in any capability to point out incorrect scientific facts or explanations for students. Additionally, to facilitate understanding of the dynam-ics of the argumentation process, researchers' intervention was intentionally minimal in this study (Asterhan, Schwarz, & Gil, 2012;White & Dinos, 2010;Zahn, Krauskopf, Hesse, & Pea, 2012). However, both researchers intervened in the process when the students were off-task or off-topic.…”
Section: Solar Teammentioning
confidence: 99%
“…One speculation is that the difference between these two types of guidance approaches may not have been operationalized in a sufficiently salient manner to result in a noticeable difference in student participation. It may have been that both social and cognitive approaches are needed to tailor to different learners' needs and learning contexts, as prior research often suggested incongruent results in different learning tasks and environments (Zahn et al, 2012). Due to many other potential factors in place that could potentially influence student learning, no conclusive remarks can be made regarding the superiority of either type of guidance approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on small group collaborative learning suggested the critical role of effective social interaction in social learning processes and outcomes (Nastasi & Clements, 1991;O'Donnell & O'Kelly, 1994). In an experimental study where middle school students' performance and learning were examined, researchers found that social-interaction-related guidance was more effective than cognitive-task-related guidance in terms of learning outcomes of achieving history knowledge and skills (Zahn, Krauskopf, Hesse, & Pea, 2012).…”
Section: Research On Instructional Guidancementioning
confidence: 99%
“…For example, Race (2013) reports that students have a tendency to switch off mentally if an instructor's assistance provides them all the answers. In a similar vein, Zahn, Krauskopf, Hesse, and Pea (2012) state that students can feel overwhelmed or become bored by an instructor's extensive instructions before they really start doing anything.…”
Section: Faded Instructor-led Attention Guidancementioning
confidence: 99%
“…From a design science perspective, this finding underscores the effectiveness of the IT artifact at hand. If the instructor's voice had been more directly and more strongly present by actively taking part in the discussion itself, that may still have had such a subduing effect (see Race, 2013 andZahn et al, 2012, for such findings).…”
Section: Rq1mentioning
confidence: 99%